High water content biomedical devices

JP2024525455A5Inactive Publication Date: 2025-04-14BAUSCH & LOMB IRELAND LIMITED
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023580539
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-06-30
Filing Date
2022-06-17
Publication Date
2025-04-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Contact lenses often cause discomfort due to dryness and eye irritation, particularly at the end of the day, despite efforts to improve comfort, and existing non-silicone hydrogels lack optimal combinations of high water content and oxygen permeability.

Method used

Biomedical devices, such as contact lenses, are formulated with glycosaminoglycan polymers grafted onto a polymeric backbone and combined with non-silicone monomers, enhancing water content and oxygen permeability while improving lubricity and stability.

Benefits of technology

The resulting devices exhibit high water content and oxygen permeability, reducing discomfort and enhancing wearability by maintaining lens lubrication and stability, with reduced enzymatic, oxidative, and thermal degradation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A biomedical device is disclosed that includes a polymerization product of a biomedical device-forming mixture that includes (a) one or more grafted glycosaminoglycan polymers that include a glycosaminoglycan having a polymer backbone and one or more side chains that include an ethylenically unsaturated reactant-containing residue grafted onto the polymer backbone, and (b) one or more non-silicone biomedical device-forming monomers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Claiming priority This application claims priority to U.S. Provisional Patent Application No. 63 / 217,006, entitled "High Water Content Biomedical Devices," filed June 30, 2021, the contents of which are incorporated by reference in their entirety herein. [Background technology]

[0002] It is highly desirable that contact lenses be as comfortable as possible for the wearer. Contact lens manufacturers are continually working to improve lens comfort. Nevertheless, many people who wear contact lenses still experience dryness or eye irritation throughout the day, especially toward the end of the day. Insufficiently wetted lenses will at some point cause significant discomfort to the lens wearer. Wetting drops can be used, if necessary, to alleviate such discomfort, but it is of course desirable to prevent such discomfort from occurring in the first place.

[0003] Glycosaminoglycans (GAGs) are a group of polysaccharides built up of repeating disaccharide units. Due to their high polarity and affinity for water, they can be found in many systems of the human and animal body. For example, GAGs occur on the surface of cells and in the extracellular matrix of animal organisms such as skin, cartilage, and lungs.

[0004] GAGs each have a chemical structure that includes a repeating basic disaccharide structure consisting of uronic acid and hexosamine, and are optionally sulfated to various degrees. GAGs are mainly classified into three groups according to the disaccharides that compose them: a first group of compounds consisting of chondroitin sulfate or dermatan sulfate, a second group of compounds consisting of heparan sulfate or heparin, and a third group of hyaluronic acid compounds. For example, compounds consisting of chondroitin sulfate or dermatan sulfate consist of disaccharide: uronic acid (glucuronic acid or iduronic acid) (β1→3) N-acetylgalactosamine, compounds consisting of heparan sulfate or heparin consist of disaccharide: uronic acid (glucuronic acid or iduronic acid) (β1→4) N-acetylglucosamine, and hyaluronic acid consists of disaccharide: glucuronic acid (β1→3) N-acetylglucosamine. In addition, due to the combination with the modification by sulfation, the structures are very diverse.

[0005] These GAGs are known as biological materials that possess both physicochemical properties derived from their characteristic viscoelasticity, depending on their molecular size and sulfation pattern, and biological properties mediated by their interactions with various functional proteins. Summary of the Invention

[0006] According to an exemplary embodiment, the biomedical device comprises the polymerization product of a biomedical device-forming mixture comprising: (a) one or more grafted glycosaminoglycan polymers comprising a glycosaminoglycan having a polymer backbone and one or more side chains comprising an ethylenically unsaturated reactant-containing residue grafted onto the polymer backbone; and (b) one or more non-silicone biomedical device-forming monomers.

[0007] According to another exemplary embodiment, a method of making a biomedical device includes (a) providing a biomedical device-forming mixture comprising (i) one or more grafted glycosaminoglycan polymers comprising a glycosaminoglycan having a polymer backbone and one or more side chains comprising an ethylenically unsaturated reactant-containing residue grafted onto the polymer backbone, and (ii) one or more non-silicone biomedical device-forming monomers; (b) subjecting the mixture to polymerization conditions to provide a polymerized biomedical device; and (c) hydrating the polymerized biomedical device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Various non-limiting exemplary embodiments described herein are directed to biomedical devices derived from one or more grafted glycosaminoglycan polymers comprising a glycosaminoglycan having a polymer backbone and one or more side chains comprising an ethylenically unsaturated reactant-containing residue grafted onto the polymer backbone, where the one or more grafted glycosaminoglycan polymers are polymerized with one or more non-silicone biomedical device-forming monomers.

[0009] In the field of biomedical devices such as contact lenses, various physical and chemical properties such as oxygen permeability, wettability, material strength, and stability are just some of the factors that must be carefully balanced to provide a usable contact lens. For example, the cornea receives its oxygen supply from contact with the atmosphere, so good oxygen permeability is an important feature for certain contact lens materials. Wettability is also important in that if the lens is not sufficiently wetted, it will not remain lubricated and therefore will not be comfortable to wear on the eye. Therefore, an optimal contact lens will have at least both good oxygen permeability and good tear wettability.

[0010] Although lenses with high water content are softer, smoother, and more comfortable to wear, such lenses may not have one or more properties useful for providing comfortable and safe wearing of contact lenses. Hydrogels represent a desirable class of materials for many biomedical applications, including contact lenses and intraocular lenses. Hydrogels are hydrated crosslinked polymer systems that contain water in equilibrium. Silicone hydrogels are a known class of hydrogels, characterized by containing siloxy-containing materials. The advantage of silicone hydrogels compared to non-silicone hydrogels is that silicone hydrogels typically have higher oxygen permeability because they contain siloxy-containing monomers. For example, the currently available non-silicone hydrogels shown in Table 1 below have the following water content and oxygen permeability (Dk): [Table 1]

[0011] The biomedical devices described in the exemplary embodiments herein overcome the shortcomings of non-silicone hydrogels mentioned above and advantageously have high water content and / or high oxygen permeability (Dk) as described below. Thus, the biomedical devices disclosed herein exhibit both suitable physical and chemical properties for prolonged contact with the body, such as oxygen permeability, lubricity, and wettability. Furthermore, the grafted glycosaminoglycan polymers used in the fabrication of the biomedical devices are believed to advantageously exhibit less enzymatic, oxidative, and thermal degradation, and therefore exhibit higher stability, longer shelf life, and desired conformational rigidity.

[0012] The biomedical devices disclosed herein are intended to be in direct contact with body tissues or fluids. As used herein, the term "biomedical device" refers to any article designed to be used either in or on mammalian tissues or fluids, preferably in or on human tissues or fluids. Representative examples of biomedical devices include, but are not limited to, artificial ureters, diaphragms, intrauterine contraceptive devices, heart valves, catheters, denture liners, prosthetic devices, and ophthalmic lens applications, where the lenses are intended to be placed directly in and on the eye, such as, for example, intraocular devices and contact lenses. In one exemplary embodiment, the biomedical device is an ophthalmic device, particularly a contact lens, and more particularly a contact lens made from silicone hydrogel.

[0013] As used herein, the term "ophthalmic device" refers to devices that reside in and on the eye. These lenses can provide optical correction, wound treatment, drug delivery, diagnostic functions, or cosmetic enhancements or effects, or a combination of these properties. Useful ophthalmic devices include, but are not limited to, ophthalmic lenses, such as soft contact lenses, e.g., soft hydrogel soft lenses, soft non-hydrogel soft lenses, hard contact lenses, e.g., hard gas permeable hard lens materials, intraocular lenses, overlay lenses, intraocular inserts, optical inserts, and the like. As will be understood by those skilled in the art, a lens is considered to be "soft" if it can fold back on itself without breaking.

[0014] In a non-limiting exemplary embodiment, the biomedical devices disclosed herein will be high water content biomedical devices. For example, in an exemplary embodiment, the high water content biomedical device will have an equilibrium water content of at least about 80 weight percent. In another exemplary embodiment, the high water content biomedical device will have an equilibrium water content of about 80 weight percent to about 90 weight percent.

[0015] In another non-limiting exemplary embodiment, the biomedical devices disclosed herein will exhibit high oxygen permeability (also referred to as Dk). For example, in one exemplary embodiment, the biomedical devices disclosed herein will exhibit an oxygen permeability of at least about 60. In one exemplary embodiment, the biomedical devices disclosed herein will exhibit an oxygen permeability of at least about 70. In one exemplary embodiment, the biomedical devices disclosed herein will exhibit an oxygen permeability reported in Dk (or barrer) units of about 60 to about 80.

[0016] In an exemplary embodiment, the biomedical devices described in the exemplary embodiments herein will contain a high water content and exhibit high oxygen permeability in any of the aforementioned ranges. For example, in an exemplary embodiment, the biomedical devices disclosed herein will have an equilibrium water content of at least about 80 weight percent and exhibit an oxygen permeability of at least about 60. In another exemplary embodiment, the biomedical devices disclosed herein will have an equilibrium water content of at least about 80 weight percent and exhibit an oxygen permeability of at least about 70. In an exemplary embodiment, the biomedical devices disclosed herein will have an equilibrium water content of about 80 weight percent to about 90 weight percent and exhibit an oxygen permeability of about 60 to about 80.

[0017] In non-limiting exemplary embodiments, the biomedical devices disclosed herein are formed from the polymerization product of a biomedical device-forming mixture that includes (a) one or more grafted glycosaminoglycan polymers that include a glycosaminoglycan having a polymer backbone and one or more side chains that include an ethylenically unsaturated reactant residue grafted onto the polymer backbone, and (b) one or more non-silicone biomedical device-forming monomers.

[0018] Glycosaminoglycans (GAGs) are one molecule with many alternating subunits. In general, GAGs are represented by the formula ABABAB, where A is a uronic acid and B is an amino sugar that may or may not be O- or N-sulfated, and the A and B units may be heterogeneous in terms of epimer content or sulfation. Any natural or synthetic polymer containing uronic acid can be used. Other GAGs are sulfated with different sugars. There are many different types of GAGs with commonly understood structures, such as chondroitin sulfate (e.g., chondroitin 4- and 6-sulfate), heparan, heparin sulfate, heparosan, dermatan, dermatan sulfate, hyaluronic acid or its salts, such as sodium or potassium hyaluronate, keratan sulfate, and other disaccharides, such as sucrose, lactulose, lactose, maltose, trehalose, cellobiose, mannobiose, and chitobiose. Glycosaminoglycans can be purchased from Sigma and many other biochemical suppliers, such as HTL Biotechnology (France). For example, in an exemplary embodiment, the GAG ​​is hyaluronic acid or its salts. In another exemplary embodiment, the GAG ​​is chondroitin sulfate.

[0019] GAGs will have reactive functional groups in the polymer backbone for grafting ethylenically unsaturated reactant residues onto the backbone.Suitable reactive functional groups in the polymer backbone include carboxylate-containing groups, hydroxyl-containing groups, silicone hydride groups, sulfur-containing groups such as thiols, and other groups that contain polymerizable functional groups such as allyl groups, vinyl groups, acrylates, methacrylamides, and the like.In addition, the sugar ring of GAGs can be opened to form aldehydes for further functionalization. GAGs for use herein may have a weight average molecular weight in the range of about 10,000 to about 3,000,000 Daltons (Da), with lower limits of about 10,000, about 20,000, about 30,000, about 40,000, about 50,000, about 60,000, about 70,000, about 80,000, about 90,000, or about 100,000, and upper limits of about 200,000, about 300,000, about 400,000, about 500,000, about 600,000, about 700,000, about 800,000, about 900,000, about 1,000,000, or up to about 2,800,000 Da, any of the lower limits may be combined with any of the upper limits.

[0020] Hyaluronic acid is a well-known, naturally occurring, water-soluble, biodegradable polymer composed of two alternatively linked sugars, D-glucuronic acid and N-acetylglucosamine, linked via alternating β-(1,4) and β-(1,3) glycosidic bonds. Hyaluronic acid is a non-sulfated GAG. The polymer is hydrophilic and highly viscous in aqueous solution at relatively low solute concentrations. It often occurs naturally as the sodium salt, sodium hyaluronate. However, other salts are contemplated herein, such as, for example, potassium hyaluronate. Methods for preparing commercially available hyaluronan and its salts are well-known. Hyaluronan can be purchased from Seikagaku Company, Clear Solutions Biotech, Inc., Pharmacia Inc., Sigma Inc., and many other suppliers, including HTL Biotechnology, Contipro and Bloomage Biotechnology Corporation. Hyaluronic acid has a repeating unit of the structure represented by the following formula: [ka] Thus, the repeating units in hyaluronic acid can be: [ka]

[0021] Generally, hyaluronic acid or its salts can have from about 2 to about 1,500,000 disaccharide units. In one embodiment, the hyaluronic acid or salt thereof may have a weight average molecular weight in the range of about 10,000 to about 3,000,000 Da, with a lower limit of about 10,000, about 20,000, about 30,000, about 40,000, about 50,000, about 60,000, about 70,000, about 80,000, about 90,000, or about 100,000, and an upper limit of about 200,000, about 300,000, about 400,000, about 500,000, about 600,000, about 700,000, about 800,000, about 900,000, about 1,000,000, or up to about 2,800,000 Da, and any of the lower limits may be combined with any of the upper limits.

[0022] Chondroitin sulfate is a linear sulfated polysaccharide composed of repeating β-D-glucuronic acid (GlcA) and N-acetyl-β-D-galactosamine (GalNAc) units arranged in a sequence by GlcA-β(1,3)-GalNAc-β(1,4) glycosidic bonds. In one embodiment, chondroitin sulfate has one or more repeating units of the structure represented by the following formula: [ka]

[0023] In an exemplary embodiment, chondroitin sulfate has repeating units of the structure represented by the following formula: [ka]

[0024] Generally, chondroitin sulfate can have from about 2 to about 1,500,000 repeating units. In one embodiment, the chondroitin sulfate can have a weight average molecular weight in the range of about 10,000 to about 3,000,000 Da, with the lower limit being about 5,000, 10,000, about 20,000, about 30,000, about 40,000, about 50,000, about 60,000, about 70,000, about 80,000, about 90,000, or about 100,000, and the upper limit being about 200,000, about 300,000, about 400,000, about 500,000, about 600,000, about 700,000, about 800,000, about 900,000, about 1,000,000, or about 3,000,000 Da, and any of the lower limits can be combined with any of the upper limits.

[0025] In one embodiment, dermatan sulfate has a repeating unit having a structure represented by the following formula: [ka]

[0026] In general, dermatan sulfate can have from about 2 to about 1,500,000 repeating units. In one embodiment, the chondroitin sulfate can have a weight average molecular weight in the range of about 10,000 to about 3,000,000 Da, with the lower limit being about 5,000, 10,000, about 20,000, about 30,000, about 40,000, about 50,000, about 60,000, about 70,000, about 80,000, about 90,000, or about 100,000, and the upper limit being about 200,000, about 300,000, about 400,000, about 500,000, about 600,000, about 700,000, about 800,000, about 900,000, about 1,000,000, or about 3,000,000 Da, and any of the lower limits can be combined with any of the upper limits.

[0027] In an exemplary embodiment, heparin and heparin sulfate have repeating units of a structure represented by the following formula: [ka]

[0028] Generally, heparin and heparin sulfate can have from about 2 to about 1,500,000 repeating units. In one embodiment, the chondroitin sulfate can have a weight average molecular weight in the range of about 10,000 to about 3,000,000 Da, with the lower limit being about 5,000, 10,000, about 20,000, about 30,000, about 40,000, about 50,000, about 60,000, about 70,000, about 80,000, about 90,000, or about 100,000, and the upper limit being about 200,000, about 300,000, about 400,000, about 500,000, about 600,000, about 700,000, about 800,000, about 900,000, about 1,000,000, or about 3,000,000 Da, and any of the lower limits can be combined with any of the upper limits.

[0029] In embodiments, the keratan sulfate has repeating units of a structure represented by the following formula: [ka]

[0030] In general, keratan sulfate can have from about 2 to about 1,500,000 repeating units. In one embodiment, the chondroitin sulfate can have a weight average molecular weight in the range of about 10,000 to about 3,000,000 Da, with lower limits of about 5,000, 10,000, about 20,000, about 30,000, about 40,000, about 50,000, about 60,000, about 70,000, about 80,000, about 90,000, or about 100,000, and upper limits of about 200,000, about 300,000, about 400,000, about 500,000, about 600,000, about 700,000, about 800,000, about 900,000, about 1,000,000, or about 3,000,000, and any of the lower limits can be combined with any of the upper limits.

[0031] The ethylenically unsaturated reactant-containing residue grafted onto the reactive functional group in the polymer backbone of the GAG ​​is derived from a monomer that comprises an ethylenically unsaturated reactive group and at least one reactive end group. In one embodiment, the ethylenically unsaturated reactant-containing residue is a methacrylate-containing residue. The at least one reactive end group comprises a reactive functional group that can be grafted onto a complementary reactive functional group in the polymer backbone of the GAG. Suitable reactive functional groups of the monomer that comprises an ethylenically unsaturated reactive group and at least one reactive end group include, for example, halogen, anhydride, amino group, aldehyde group, carboxylic acid group, alcohol group, thiol group, hydrazide group, glycidyl group, etc. In one non-limiting exemplary embodiment, the ethylenically unsaturated reactant-containing residue may be derived from, for example, methacrylic anhydride, methacryloyl chloride, 2-isocyanoethyl methacrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-(chlorodimethylsilyl)propyl methacrylate, glycidyl methacrylate, methacryloyl hydrazide, aminoethyl methacrylate, vinyl chloroformate, allyl chloride, acryloyl chloride, and acrylic anhydride. However, other monomers are contemplated for forming the ethylenically unsaturated reactant-containing residue on the polymer backbone of the GAG, and the foregoing list is merely illustrative.

[0032] The grafted glycosaminoglycan polymers disclosed herein can be obtained by grafting at least one reactive end group of one or more monomers containing an ethylenically unsaturated reactive group onto a complementary reactive functional group in the polymer backbone of the glycosaminoglycan. For example, in one exemplary embodiment, an anhydride group of one or more monomers containing an ethylenically unsaturated reactive group can be grafted onto a carboxylic acid group in the polymer backbone of the glycosaminoglycan. In a non-limiting exemplary embodiment, the graft polymerization reaction can provide a degree of grafting, i.e., the number of side chains in the polymer backbone that contain ethylenically unsaturated reactant-containing residues, in the range of about 0.5 to about 50%. In another exemplary embodiment, the degree of grafting can be in the range of about 2 to about 30%. In another exemplary embodiment, the degree of grafting can be in the range of about 5 to about 20%. In yet another exemplary embodiment, the degree of grafting can be in the range of about 5 to about 15%. In yet another exemplary embodiment, the degree of grafting can be in the range of about 5 to about 10%.

[0033] Generally, the GAG ​​and the monomer containing an ethylenically unsaturated reactive group and at least one reactive end group can be added sequentially or simultaneously to the reaction mixture. The reaction can be carried out at a suitable temperature and for a period of time to complete the reaction to maximize the yield of the product ethylenically unsaturated reactant-containing residue grafted onto the polymer backbone of the glycosaminoglycan. For example, suitable temperatures and periods include temperatures in the range of about 10 to about 40° C. and periods in the range of about 4 hours to about 48 hours. In an exemplary embodiment, suitable temperatures and periods include temperatures in the range of about 15 to about 25° C. and periods in the range of about 8 hours to about 24 hours.

[0034] In an exemplary embodiment, the glycosaminoglycan can be added to the reaction mixture in an amount ranging from about 0.5% to about 5% by weight, based on the total weight of the reaction mixture. In an exemplary embodiment, the glycosaminoglycan can be added to the reaction mixture in an amount ranging from about 1% to about 3% by weight, based on the total weight of the reaction mixture.

[0035] In an exemplary embodiment, the monomer comprising an ethylenically unsaturated reactive group and at least one reactive end group can be added to the reaction mixture in an amount ranging from about 0.1% to about 5% by weight, based on the total weight of the reaction mixture. In one exemplary embodiment, the monomer comprising an ethylenically unsaturated reactive group and at least one reactive end group can be added to the reaction mixture in an amount ranging from about 0.5% to about 2% by weight, based on the total weight of the reaction mixture.

[0036] In a non-limiting exemplary embodiment, the ethylenically unsaturated reactant-containing residue is a methacrylate-containing residue derived from the methacrylate-containing monomers described above, and the degree of methacrylation can range from about 0.5 to about 50%. In another exemplary embodiment, the degree of methacrylation can range from about 2 to about 30%. In yet another exemplary embodiment, the degree of methacrylation can range from about 5 to about 15%.

[0037] The resulting grafted glycosaminoglycan polymers can be random or block copolymers. In an exemplary embodiment, the grafted glycosaminoglycan polymers disclosed herein can have a weight average molecular weight in the range of about 20,000 to about 6,000,000 Da, with lower limits of about 20,000, about 30,000, about 40,000, about 50,000, about 60,000, about 70,000, about 80,000, about 90,000, or about 100,000 Da, and upper limits of about 100,000, about 15,000, about 20,000, about 30,000, about 40,000, about 50,000, about 60,000, about 70,000, about 80,000, about 90,000, or about 100,000 Da. 0,000, about 200,000, about 300,000, about 400,000, about 500,000, about 600,000, about 700,000, about 800,000, about 900,000, about 1,000,000, about 2,000,000, about 3,000,000, about 4,000,000, about 5,000,000, or up to about 6,000,000 Da, any of the lower limits may be combined with any of the upper limits.

[0038] The resulting grafted glycosaminoglycan polymer may be present in the biomedical device-forming mixture in an amount ranging from about 0.1 to about 2 weight percent, based on the total weight of the biomedical device-forming mixture. In another embodiment, the resulting grafted glycosaminoglycan polymer may be present in the biomedical device-forming mixture in an amount ranging from about 0.25 to about 1.5 weight percent, based on the total weight of the biomedical device-forming mixture.

[0039] In a non-limiting exemplary embodiment, the one or more non-silicone biomedical device-forming monomers suitable for inclusion in the biomedical device-forming mixture include, for example, one or more non-silicone hydrophilic monomers. Representative examples of the one or more non-silicone hydrophilic monomers include unsaturated carboxylic acids, acrylamides, vinyl lactams, poly(alkyleneoxy)(meth)acrylates, hydroxyl-containing (meth)acrylates, hydrophilic vinyl carbonates, hydrophilic vinyl carbamates, hydrophilic oxazolones, and poly(alkene glycols) functionalized with polymerizable groups, and mixtures thereof. Representative examples of unsaturated carboxylic acids include methacrylic acid, acrylic acid, and mixtures thereof. Representative examples of amides include alkylamides, such as N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, and mixtures thereof. Representative examples of cyclic lactams include N-vinyl-2-pyrrolidone, N-vinylcaprolactam, N-vinyl-2-piperidone, and mixtures thereof. Representative examples of hydroxyl-containing (meth)acrylates include 2-hydroxyethyl methacrylate, glycerol methacrylate, and the like, and mixtures thereof. Representative examples of functionalized poly(alkene glycols) include poly(diethylene glycols) of various chain lengths containing monomethacrylate or dimethacrylate end caps. In one embodiment, the poly(alkene glycol) polymer contains at least two alkene glycol monomer units. Further examples are the hydrophilic vinyl carbonate or vinyl carbamate monomers disclosed in U.S. Pat. No. 5,070,215, and the hydrophilic oxazolone monomers disclosed in U.S. Pat. No. 4,910,277. Other suitable hydrophilic monomers will be apparent to those skilled in the art. Mixtures of the aforementioned non-silicone-containing hydrophilic monomers can also be used in the monomer mixtures herein.

[0040] In one exemplary embodiment, the one or more non-silicone biomedical device-forming monomers may be present in the biomedical device-forming mixture in an amount ranging from about 30 to about 90 weight percent, based on the total weight of the biomedical device-forming mixture. In another exemplary embodiment, the one or more non-silicone biomedical device-forming monomers may be present in the biomedical device-forming mixture in an amount ranging from about 45 to about 75 weight percent, based on the total weight of the biomedical device-forming mixture.

[0041] In an exemplary embodiment, the biomedical device-forming mixture can further include one or more hydrophobic monomers. Suitable hydrophobic monomers include, for example, ethylenically unsaturated hydrophobic monomers, such as (meth)acrylate-containing hydrophobic monomers, N-alkyl (meth)acrylamide-containing hydrophobic monomers, alkyl vinyl carbonate-containing hydrophobic monomers, alkyl vinyl carbamate-containing hydrophobic monomers, fluoroalkyl (meth)acrylate-containing hydrophobic monomers, N-fluoroalkyl (meth)acrylamide-containing hydrophobic monomers, N-fluoroalkyl vinyl carbonate-containing hydrophobic monomers, N-fluoroalkyl vinyl carbamate-containing hydrophobic monomers, silicone-containing (meth)acrylate-containing hydrophobic monomers, (meth)acrylamide-containing hydrophobic monomers, vinyl carbonate-containing hydrophobic monomers, vinyl carbamate-containing hydrophobic monomers, styrene-containing hydrophobic monomers, and polyoxypropylene (meth)acrylate-containing hydrophobic monomers, and mixtures thereof. As used herein, the term "(meth)" refers to an optional methyl substituent. Thus, a term such as "(meth)acrylate" refers to either methacrylate or acrylate, and "(meth)acrylamide" refers to either methacrylamide or acrylamide.

[0042] In one non-limiting exemplary embodiment, the one or more hydrophobic monomers are represented by the structure of Formula I: [ka] In the formula, R1 is methyl or hydrogen, R 2 is -O- or -NH-, R 3 and R 4 are independently -CH2-, -CHOH-, and -CHR 6 -, R 5 and R 6 is independently a branched C3-C8 alkyl group; R 7 is hydrogen or —OH; n is an integer of at least 1; and m and p are independently 0 or an integer of at least 1, with the proviso that the sum of m, p, and n is 2, 3, 4, or 5.

[0043] Representative examples of the one or more hydrophobic monomers represented by the structure of formula I include, but are not limited to, 4-t-butyl-2-hydroxycyclohexyl methacrylate (TBE), 4-t-butyl-2-hydroxycyclopentyl methacrylate, 4-t-butyl-2-hydroxycyclohexyl methacrylamide (TBA), 6-isopentyl-3-hydroxycyclohexyl methacrylate, 2-isohexyl-5-hydroxycyclopentyl methacrylamide, 4-t-butylcyclohexyl methacrylate, isobornyl methacrylate, adamantyl methacrylate, n-butyl methacrylate, n-hexyl methacrylate, lauryl methacrylate, and benzyl methacrylate. In one embodiment, the one or more hydrophobic monomers comprise a compound of formula I, wherein R 3 is -CH2-, m is 1 or 2, p is 0, and the sum of m and n is 3 or 4.

[0044] In an exemplary embodiment, the one or more hydrophobic monomers will be present in the biomedical device forming mixture in an amount ranging from about 0.5 to about 25 weight percent, based on the total weight of the mixture, hi another embodiment, the one or more hydrophobic monomers will be present in the biomedical device forming mixture in an amount ranging from about 1 to about 10 weight percent, based on the total weight of the biomedical device forming mixture.

[0045] In non-limiting exemplary embodiments, the biomedical device forming mixture further comprises one or more crosslinkers. Crosslinkers suitable for use herein are known to those skilled in the art. In exemplary embodiments, the one or more crosslinkers are bifunctional or multifunctional crosslinkers that contain two or more reactive functional groups. In embodiments, the one or more crosslinkers have at least two polymerizable functional groups. Representative examples of crosslinkers include divinylbenzene, allyl methacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,4-butanediol diglycidyl ether, polyethylene glycol dimethacrylate, vinyl carbonate derivatives of glycol dimethacrylate, and methacryloxyethyl vinyl carbonate. However, other crosslinkers are contemplated, and the foregoing list is merely exemplary.

[0046] In exemplary embodiments, the one or more crosslinking agents are used in an amount of less than about 5% by weight, and generally less than about 2% by weight, e.g., from about 0.1 to about 5% by weight, or from about 0.1 to about 2% by weight, based on the total weight of the biomedical device-forming mixture.

[0047] In an exemplary embodiment, the biomedical device-forming mixture may further include one or more humectants. In one embodiment, suitable one or more humectants include, for example, poly(vinyl alcohol) (PVA), poly(N-vinylpyrrolidone) (PVP), polymers containing carboxylic acid functionality, such as polymers containing poly(acrylic acid) (PAA), copolymers of the foregoing, and the like. Another suitable class of humectants includes non-polymeric humectants. Representative examples of such humectants include glycerin, propylene glycol, and other non-polymeric diols and glycols.

[0048] In an exemplary embodiment, the one or more humectants can be present in the biomedical device-forming mixture in an amount ranging from about 0 to about 10 wt %, based on the total weight of the biomedical device-forming mixture. In another embodiment, the one or more humectants can be present in the biomedical device-forming mixture in an amount ranging from about 0.1 to about 10 wt %, based on the total weight of the biomedical device-forming mixture. In yet another embodiment, the one or more humectants can be present in the biomedical device-forming mixture in an amount ranging from about 0.5 to about 5 wt %, based on the total weight of the biomedical device-forming mixture.

[0049] In an exemplary embodiment, the biomedical device forming mixture can further include one or more surfactants, such as end-functionalized surfactants. Suitable end-functionalized surfactants include, for example, one or more end-functionalized polyethers. Useful polyethers to be end-functionalized include one or more chains or polymeric moieties having one or more (-OR-) repeat units, where R is an alkylene or arylene group having from 2 to about 6 carbon atoms. The polyethers can be derived from block copolymers formed from different ratios of ethylene oxide (EO) and propylene oxide (PO) moieties. Such polyethers and their respective component fragments can include different attached hydrophobic and hydrophilic chemical functional moieties and fragments.

[0050] Representative examples of suitable polyethers that can be end-functionalized are poloxamer block copolymers. One particular class of poloxamer block copolymers are those available under the trademark Pluronic (BASF Wyandotte Corp., Wyandotte, Mich.). Poloxamers include Pluronics and reverse Pluronics. Pluronics are a series of ABA block copolymers consisting of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) blocks, generally as represented by Formula II: HO(C2H4O) a (C3H6O) b(C2H4O) a H (II) wherein a is independently at least 1 and b is at least 1.

[0051] Reverse Pluronics are a series of BAB block copolymers generally consisting of poly(propylene oxide)-poly(ethylene oxide)-poly(propylene oxide) blocks as represented by Formula III: HO(C3H6O) b (C2H4O) a (C3H6O) b H (III) where a is at least 1 and b is independently at least 1. The poly(ethylene oxide) (PEO) blocks are hydrophilic, whereas the poly(propylene oxide) (PPO) blocks are hydrophobic in nature. Each series of poloxamers has a different ratio of PEO to PPO that ultimately determines the hydrophilic-lipophilic balance (HLB) of the material, i.e., the different HLB values ​​are based on different values ​​of a and b, where a represents the number of hydrophilic poly(ethylene oxide) units (PEO) present in the molecule and b represents the number of hydrophobic poly(propylene oxide) units (PPO) present in the molecule.

[0052] Poloxamers and reverse poloxamers have terminal hydroxyl groups that can be end-functionalized. An example of an end-functionalized poloxamer is poloxamer dimethacrylate (e.g., Pluronic® F127 dimethacrylate) as disclosed in U.S. Patent Application Publication No. 2003 / 0044468, as discussed herein below. Other examples include glycidyl-terminated copolymers of polyethylene glycol and polypropylene glycol as disclosed in U.S. Patent No. 6,517,933.

[0053] Another example of a suitable polyether that can be end-functionalized is a poloxamine block copolymer. While poloxamers and reverse poloxamers are considered to be difunctional molecules (based on the terminal hydroxyl groups), poloxamines are in tetrafunctional form, i.e., these molecules are tetrafunctional block copolymers terminated with primary hydroxyl groups and linked by a central diamine. One particular class of poloxamine block copolymers is available under the trademark Tetronic (BASF). Poloxamines include Tetronics and reverse Tetronics. Poloxamines have the general structure of formula IV: [ka] wherein a is independently at least 1 and b is independently at least 1.

[0054] The poloxamer and / or poloxamine are functionalized to provide the desired reactivity at the end of the molecule. The functionality can vary and is determined based on the intended use of the functionalized PEO- and PPO-containing block copolymers. That is, the PEO- and PPO-containing block copolymers are reacted to provide a terminal functionality that is complementary to the intended device-forming monomer mixture. The term block copolymer as used herein should be understood to mean a poloxamer and / or poloxamine having two or more blocks in the polymer backbone.

[0055] In general, the selection of functional end groups is determined by the functional groups of the reactive molecules in the mixture. For example, if the reactive molecule contains a carboxylic acid group, glycidyl methacrylate can provide a methacrylate end group. If the reactive molecule contains a hydroxy or amino functional group, isocyanatoethyl methacrylate or (meth)acryloyl chloride can provide a methacrylate end group, and vinyl chloroformate can provide a vinyl end group. A variety of suitable combinations of ethylenically unsaturated end groups and reactive molecules will be apparent to those skilled in the art. For example, the functional group may comprise a moiety selected from amines, hydrazines, hydrazides, thiols (nucleophiles), carboxylic acids, carboxylic esters including imidoesters, orthoesters, carbonates, isocyanates, isothiocyanates, aldehydes, ketones, thiones, alkenyls, acrylates, methacrylates, acrylamides, sulfones, maleimides, disulfides, iodos, epoxies, sulfonates, thiosulfonates, silanes, alkoxysilanes, halosilanes, and phosphoramidates. More specific examples of these groups include succinimidyl esters or carbonates, imidazolyl esters or carbonates, benzotriazole esters or carbonates, p-nitrophenyl carbonates, vinyl sulfones, chloroethyl sulfones, vinyl pyridines, pyridyl disulfides, iodoacetamides, glyoxals, diones, mesylates, tosylates, and tresylates. Also included are other activated carboxylic acid derivatives, as well as hydrates or protected derivatives of any of the above moieties (e.g., aldehyde hydrates, hemiacetals, acetals, ketone hydrates, hemiketals, ketals, thioketals, thioacetals).Preferred electrophilic groups include succinimidyl carbonates, succinimidyl esters, maleimides, benzotriazole carbonates, glycidyl ethers, imidazoyl esters, p-nitrophenyl carbonates, acrylates, tresylates, aldehydes, and orthopyridyl disulfides.

[0056] Representative examples of reaction sequences by which the PEO- and PPO-containing block copolymers can be end-functionalized are set forth below. [ka]

[0057] Further provided herein are certain illustrative but non-limiting examples of reactions for providing functionalized ends for PEO- and PPO-containing block copolymers. It should be understood that those skilled in the art can determine other reaction methods without undue experimentation. It should also be understood that any particular block copolymer molecule shown is only one chain length of a polydisperse population of the referenced material.

[0058] In an exemplary embodiment, the biomedical device forming mixture includes one or more of a PEO-containing block copolymer and a PPO-containing block copolymer. One example of such a copolymer that may be used in the monomer mixture is Pluronic® F127, [(polyethylene oxide) 99 -(Polypropylene oxide) 66 -(Polyethylene oxide) 99 The terminal hydroxyl groups of this copolymer are functionalized to allow the copolymer to react with other ophthalmic device forming monomers. Another example is Pluronic 407 dimethacrylate, which has the structure: [ka]

[0059] In an exemplary embodiment, the end-functionalized surfactant is selected from the group consisting of a poloxamer having at least one end-functionalized portion, a reverse poloxamer having at least one end-functionalized portion, a poloxamine having at least one end-functionalized portion, a reverse poloxamine having at least one end-functionalized portion, and mixtures thereof.

[0060] In an exemplary embodiment, the surfactant may be present in the biomedical device forming mixture in an amount ranging from about 0.01 to about 20% by weight, based on the total weight of the biomedical device forming mixture. In another exemplary embodiment, the surfactant may be present in the biomedical device forming mixture in an amount ranging from about 1 to about 10% by weight, based on the total weight of the biomedical device forming mixture.

[0061] In another exemplary embodiment, the biomedical device forming mixture can further include one or more ultraviolet (UV) blocking agents. In one embodiment, useful UV blocking agents include one or more compounds of the following formula: [ka] (2-propenoic acid, 2-methyl, 2-(4-benzoyl-3-hydroxyphenoxy)-1-[(4-benzoyl 3-hydroxyphenoxy)methyl ester), [ka]

[0062] The biomedical device-forming mixture disclosed herein may further contain various additives, such as antioxidants, colorants, strengthening agents, and other components well known in the art, as needed, within the scope of not impairing the purpose and effect of the exemplary embodiments disclosed herein.

[0063] Exemplary embodiment biomedical devices, such as contact lenses or intraocular lenses, can be prepared by polymerizing the biomedical device-forming mixture described above to form a product that can then be formed into a suitable shape, for example, by lathing, injection molding, compression molding, cutting, etc. For example, in manufacturing contact lenses, the initial mixture may be polymerized in a tube to provide rod-like articles that are then cut into buttons. The buttons may then be lathed into contact lenses.

[0064] Alternatively, biomedical devices such as contact lenses may be cast directly from the mixture in a mold, e.g., a polypropylene mold, by, for example, spin casting and static casting. Spin casting is disclosed in U.S. Pat. Nos. 3,408,429 and 3,660,545, and static casting is disclosed in U.S. Pat. Nos. 4,113,224, 4,197,266, and 5,271,875. Spin casting involves filling a mold with the mixture to be polymerized and rotating the mold in a controlled manner while exposing the mixture to a radiation source, such as UV light. Static casting involves filling a monomer mixture between two mold parts, one mold part shaped to form the anterior surface of the lens and the other mold part shaped to form the posterior surface of the lens, and curing the mixture while held in the mold assembly to form the lens, e.g., by free radical polymerization of the mixture.

[0065] Examples of free radical reaction techniques for curing lens materials include thermal radiation, infrared radiation, electron beam radiation, gamma radiation, and ultraviolet (UV) radiation, or a combination of such techniques may be used. US Patent No. 5,271,875 describes a static casting method that allows for the molding of a finished lens in a mold cavity defined by a back mold and a front mold. As an additional method, US Patent No. 4,555,732 discloses a process in which the excess mixture is cured by spin casting in a mold to form a molded article having a lens front surface and a relatively large thickness, and the posterior surface of the cured spin cast article is then lathed to provide a contact lens with a desired thickness and lens posterior surface.

[0066] Polymerization may be promoted by exposing the mixture to heat and / or radiation, such as ultraviolet light, visible light, or high-energy radiation. A polymerization initiator may be included in the mixture to promote the polymerization step. Representative examples of free radical thermal polymerization initiators include organic peroxides, such as acetyl peroxide, lauroyl peroxide, decanoyl peroxide, stearoyl peroxide, benzoyl peroxide, peroxypivalate, and peroxydicarbonate. Representative UV initiators are known in the art and include benzoin methyl ether, benzoin ethyl ether, Darocure® 1173, 1164, 2273, 1116, 2959, 3331 (EM Industries), and Irgacure® 651, 184, and 2959 (Ciba-Geigy), 2,2' azobis(2-methylpropionitrile) (VAZO 64), and the like. Generally, the initiator will be used in the mixture at a concentration of from about 0.01 to about 5 weight percent of the total mixture.

[0067] The polymerization is generally carried out in a reaction medium such as a solvent or dispersion using a solvent such as water or an alkanol containing 1 to 4 carbon atoms such as methanol, ethanol, or propan-2-ol. Alternatively, a mixture of any of the above solvents may be used.

[0068] Generally, the polymerization can be carried out under an inert atmosphere of, for example, nitrogen or argon, for about 15 minutes to about 72 hours. If desired, the resulting polymerization product can be dried under vacuum, for example, for about 5 to about 72 hours, or left in an aqueous solution before use.

[0069] Polymerization of the mixture results in a polymer that, when hydrated, preferably forms a hydrogel. When producing hydrogel lenses, the mixture may further include at least one diluent that will eventually be replaced by water when the polymerization product is hydrated to form a hydrogel. The amount of diluent used should be less than about 50% by weight, and in most cases the diluent content will be less than about 30% by weight. However, for a particular polymer system, the practical limit will be determined by the solubility of the various monomers in the diluent. To produce an optically clear copolymer, it is important that no phase separation occurs between the comonomer and the diluent, or between the diluent and the final copolymer, which would result in visual opacity.

[0070] Additionally, the maximum amount of diluent that can be used will depend on the amount of swelling the diluent causes to the final polymer. Excessive swelling can cause or disintegrate the copolymer when the diluent is replaced by water upon hydration. Suitable diluents include, but are not limited to, ethylene glycol, glycerin, liquid poly(ethylene glycol), alcohol, alcohol / water mixtures, ethylene oxide / propylene oxide block copolymers, low molecular weight linear poly(2-hydroxyethyl methacrylate), glycol esters of lactic acid, formamides, ketones, dialkyl sulfoxides, butyl carbitol, and the like, and mixtures thereof.

[0071] It may be desirable to remove residual diluent from the lens prior to the edge finishing operation, which can be accomplished by evaporation at or near ambient pressure, or under vacuum, if desired. High temperatures can be used to reduce the time required to evaporate the diluent. The time, temperature, and pressure conditions for the solvent removal step will vary depending on factors such as the volatility of the diluent and the particular monomeric components, as can be readily determined by one of ordinary skill in the art. If desired, the mixture used to make hydrogel lenses may further include crosslinkers and wetting agents known in the prior art for making hydrogel materials.

[0072] In the case of intraocular lenses, the monomer mixture to be polymerized may further include a monomer to increase the refractive index of the resulting polymerization product. Examples of such monomers include aromatic (meth)acrylates, such as phenyl (meth)acrylate, 2-phenylethyl (meth)acrylate, 2-phenoxyethyl methacrylate, and benzyl (meth)acrylate.

[0073] The biomedical devices obtained herein, such as contact lenses, may be subjected to optional machining operations. For example, other optional machining steps may include buffing or polishing of the lens edges and / or surfaces. In general, such machining processes may be performed before or after the product is released from the mold parts, for example, the lens is dry demolded from the mold by lifting the lens from the mold with vacuum tweezers, after which the lens is transferred by mechanical tweezers to a second set of vacuum tweezers and placed against a rotating surface to smooth the surface or edges. The lens may then be flipped over to machine the other side of the lens.

[0074] The lenses may then be transferred to individual lens packages containing a buffered saline solution. Saline may be added to the package either before or after transfer of the lenses. Suitable package designs and materials are known in the art. The plastic package is peelably sealed with a film. Suitable sealing films are known in the art and include foils, polymeric films, and mixtures thereof. The sealed package containing the lenses is then sterilized to ensure a sterile product. Suitable sterilization means and conditions are known in the art and include, for example, autoclaving.

[0075] As one of ordinary skill in the art would readily appreciate, other steps can be included in the above-described molding and packaging process, including, for example, coating the formed lenses, surface treating the lenses during formation (e.g., via mold transfer), inspecting the lenses, discarding defective lenses, cleaning mold halves, and reusing mold halves, as well as combinations thereof.

[0076] The following examples are provided to enable one of ordinary skill in the art to practice the invention and are merely illustrative and should not be read as limiting the scope of the invention as defined by the claims.

[0077] As discussed below, various polymerization products were formed and characterized by standard test procedures as follows.

[0078] Moisture content: Two sets of six hydrated lenses or films are blotted dry on a piece of filter paper to remove excess water and the samples are weighed (wet weight). The samples are then placed in a jar containing desiccant and heated in a microwave oven for 10 minutes. The samples are then allowed to stand for 30 minutes to equilibrate to room temperature and reweighed (dry weight). The moisture content is calculated from the wet and dry weights.

[0079] Contact angle: Captive bubble contact angle data was collected on a First Ten Angstroms FTA-1000 prop Shape Instrument. All samples were rinsed in HPLC grade water prior to analysis to remove components of the packaging solution from the sample surface. Prior to data collection, the surface tension of the water used for all experiments was measured using the pendant drop method. Surface tension values ​​of 70-72 dynes / cm were expected for the water to be deemed suitable for use. All lens samples were placed on a curved sample holder and submerged in a quartz cell filled with HPLC grade water. Advancing and receding captive bubble contact angles were collected for each sample. The advancing contact angle is defined as the angle measured in water as the bubble is receding from the lens surface (water is advancing across the surface). All captive bubble data was collected using a high speed digital camera focused on the sample / bubble interface. Contact angles were calculated in digital frames just prior to the contact line movement across the sample / bubble interface. The receding contact angle is defined as the angle measured in water when an air bubble is swelling across the sample surface (the water is receding from the surface).

[0080] The film samples were immersed in borate buffered saline and the elastic modulus (g / mm) was measured according to ASTM 1708 using an Instron (Model 4502) instrument. 2 ) was measured, the approximate size of the film sample was 22 mm gauge length and 4.75 mm width, the sample further had ends forming a dog bone shape to accommodate gripping of the sample by the clamps of the Instron instrument, and was 100±50 microns thick.

[0081] Oxygen permeability (also called Dk) was determined by the following procedure. Hydrogel oxygen permeability is measured by the polarographic method (ISO 18369-4:2017, ANSI Z80.20-2016) using an O2 Permeometer Model 201T instrument (Createch, Albany, California USA) with a probe containing a central circular gold cathode and a silver anode at the end insulated from the cathode. Measurements are performed only on pre-inspected, pinhole-free, flat silicone hydrogel film samples of four different center thicknesses ranging from 70 to 700 microns. Measurements of center thickness of film samples may be measured using a Rehder ET-1 electronic thickness gauge. Other methods and / or instruments may be used as long as the oxygen permeability values ​​obtained are equivalent to the described method.

[0082] Typically, the film sample has a disk shape. Measurements are performed with the film sample and probe immersed in a bath containing circulating phosphate buffered saline (PBS) equilibrated at 35°C ± 0.2°. Before immersing the probe and film sample in the PBS bath, the film sample is placed and centered on the positive electrode pre-wetted with equilibrated PBS, making sure there are no air bubbles or excess PBS between the positive electrode and the film sample, and then the film sample is secured to the probe with a mounting cap, with the positive electrode part of the probe in contact only with the film sample. For silicone hydrogel films, it is often useful to use a Teflon polymer film, for example having a disk shape, between the probe cathode and the film sample. In such cases, the Teflon film is first placed on the pre-wetted positive electrode, and then the film sample is placed on the Teflon film, making sure there are no air bubbles or excess PBS under the Teflon film or film sample. Once measurements are collected, only data with a correlation coefficient value (R2) of 0.97 or greater need to be entered into the calculation of the Dk value.

[0083] At least two Dk measurements per thickness, and R 2Obtain data that meets the values. Using known regression analysis, calculate oxygen permeability (Dk) from film samples with at least three different thicknesses. Any film samples hydrated with solutions other than PBS are first immersed in purified water and equilibrated for at least 24 hours, then immersed in PHB and equilibrated for at least 12 hours. Clean the instrument periodically and calibrate it regularly using RGP standards. Upper and lower limits are established by calculating ±20% of the repository values ​​established by William J. Benjamin, et al., The Oxygen Permeability of Reference Materials, Optom Vis Sci 7(12s):95(1997), the disclosure of which is incorporated herein in its entirety. [Table A]

[0084] In the examples, the following abbreviations are used:

[0085] HA: Hyaluronic acid

[0086] HA-MA: Methacrylated hyaluronic acid represented by the following structure: [ka]

[0087] DMA: N,N-Dimethylacetamide

[0088] EGDMA: Ethylene glycol dimethacrylate

[0089] TEGDMA: Tetraethylene glycol dimethacrylate

[0090] BDDE: 1,4-butanediol diglycidyl ether

[0091] Irgacure 2959: 2-Hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone

[0092] Irgacure 2959 (10% sln): 10% Irgacure 2959 in methanol

[0093] PVP: Polyvinylpyrrolidone (K90)

[0094] PAA: Polyacrylic acid (250kDa Mw)

[0095] POx 200: Poly(2-ethyl-2-oxazoline) (200 kDa)

[0096] POx 500: Poly(2-ethyl-2-oxazoline) (500 kDa)

[0097] P407DM: Poloxamer 407 dimethacrylate having the following structure: [ka]

[0098] Example 1 Preparation of HA-MA.

[0099] A 1-liter flask equipped with a stir bar was charged with DI water (490 mL). HA (10 g, M n Approximately 48 kDa) was dissolved in the stirred solution. A pH meter was immersed in the HA solution. Methacrylic anhydride (11.47 g, 74.3 mmol) was added to the solution at room temperature. The pH of the solution was maintained between 8.0-8.5 by adding NaOH solution (20 wt%) for 6 h, then the solution was stirred overnight. The product was purified by dialysis (MWCO 6-8 kDa) against reverse osmosis (RO) water for 2 days, followed by freeze-drying for 2 days. The product was redissolved in 300 mL of deionized (DI) water and purified again by dialysis and freeze-drying to obtain a white powder of HA-MA containing 45% methacrylate.

[0100] Example 2 Preparation of HA-MA.

[0101] A 1-liter flask equipped with a stir bar was charged with DI water (490 mL). HA (10 g, M n Approximately 115 kDa) was dissolved in the stirred solution. A pH meter was immersed in the HA solution. Methacrylic anhydride (1.91 g, 12.4 mmol) was added to the solution at room temperature. The pH of the solution was maintained at 8.0-8.5 by adding NaOH solution (20 wt%) for 6 h, then the solution was stirred overnight. The product was purified by dialysis (MWCO 6-8 kDa) against RO water for 2 days, followed by freeze-drying for 2 days. The product was redissolved in 300 mL DI water and purified again by dialysis and freeze-drying to obtain a white powder of HA-MA containing 10% methacrylate.

[0102] Examples 3 to 7 Preparation of contact lenses.

[0103] The wetting agent solutions used in the following examples were prepared as follows: A 50 mL flask was charged with a stir bar with 3.5 g of the selected wetting agent (i.e., PAA, PVP, POx200, and POx500), and 16.5 g of purified HO. The flask was then placed on a stir plate and the mixture was stirred for at least 2 hours until the wetting agent was completely dissolved, resulting in a 17.5% masterbatch solution that was stored until use.

[0104] Contact lenses were prepared using the reaction components listed in Table 2 below, in amounts per weight percent. The lenses were prepared by mixing the reaction components together in a scintillation vial with stirring or rolling for at least about 1 hour until all components were dissolved. The reaction mixture was then dispensed into a thermoplastic contact lens mold assembly and irradiated with UV light for 20 seconds to form a contact lens. The resulting lenses were demolded from the mold, extracted with water for 3 minutes, and placed in a buffered saline solution to remove residual monomer.

[0105] Once the lenses are extracted, they are placed into vials or blister packages filled with buffered saline. The vials or blisters are sealed with stoppers or foil and autoclaved at about 121° C. for about 30 minutes. The properties of the resulting contact lenses are also shown in Table 3 below. [Table 2] [Table 3]

[0106] Examples 8 to 10 Preparation of contact lenses.

[0107] Contact lenses were prepared using the reaction components listed in Table 4 below, in amounts per weight percent. The lenses were prepared by mixing the reaction components together in a scintillation vial with stirring or rolling for at least about 1 hour until all components were dissolved. The reaction mixture was then dispensed into a thermoplastic contact lens mold assembly and irradiated with UV light for 20 seconds to form a contact lens. The resulting lenses were demolded from the mold, extracted with water for 3 minutes, and placed in a buffered saline solution to remove residual monomer.

[0108] Once the lenses were extracted, they were placed into vials or blister packages filled with buffered saline. The vials or blisters were sealed with stoppers or foil and autoclaved at about 121° C. for about 30 minutes. The properties of the resulting contact lenses are also shown in Table 5 below. [Table 4] [Table 5]

[0109] For the sake of brevity, various features disclosed herein are described in the context of a single embodiment, but may be provided separately or in any suitable subcombination.All combinations of the embodiments are specifically encompassed by the exemplary embodiments disclosed herein, as if each and every combination were individually and expressly disclosed herein.In addition, all subcombinations listed in the embodiments that describe such variations are also specifically encompassed by the composition, as if each and every combination were individually and expressly disclosed herein.

[0110] It will be understood that various modifications can be made to the embodiments disclosed herein. Thus, the above description should not be construed as limiting, but merely as exemplifications of preferred embodiments. For example, the functions described above and implemented as the best mode for carrying out the invention are for illustrative purposes only. Those skilled in the art can implement other configurations and methods without departing from the scope and spirit of the invention. Moreover, those skilled in the art will envision other modifications within the scope and spirit of the features and advantages attached hereto.

Claims

1. A biomedical device comprising the polymerization product of a biomedical device-forming mixture comprising: (a) one or more grafted glycosaminoglycan polymers comprising a glycosaminoglycan having a polymer backbone and one or more side chains comprising an ethylenically unsaturated reactant-containing residue grafted onto said polymer backbone; and (b) one or more non-silicone biomedical device-forming monomers, wherein said biomedical device has a water content of at least 80% by weight.

2. 2. The biomedical device of claim 1, wherein the glycosaminoglycan is selected from the group consisting of chondroitin, chondroitin sulfate, dermatan, dermatan sulfate, heparin, heparan sulfate, heparosan, hyaluronan, and hyaluronic acid or a salt thereof.

3. 10. The biomedical device of claim 1, wherein the ethylenically unsaturated reactant-containing residue is a methacrylate-containing residue.

4. The biomedical device of claim 1, wherein the one or more non-silicone biomedical device-forming monomers include one or more non-silicone hydrophilic monomers.

5. The biomedical device of claim 4, wherein the one or more non-silicone hydrophilic monomers are selected from the group consisting of unsaturated carboxylic acids, acrylamides, vinyl lactams, poly(alkyleneoxy) (meth)acrylates, (meth)acrylic acid, hydroxyl-containing (meth)acrylates, hydrophilic vinyl carbonates, hydrophilic vinyl carbamate monomers, hydrophilic oxazolone monomers, and mixtures thereof.

6. The biomedical device of claim 1, wherein the biomedical device forming mixture further comprises one or more wetting agents selected from the group consisting of crosslinkers, lubricants, surfactants, and ultraviolet (UV) blockers.

7. The biomedical device forming mixture comprising: 0.1 to 2 weight percent of the one or more grafted glycosaminoglycan polymers, based on the total weight of the biomedical device forming mixture; 10. The biomedical device of claim 1, comprising 30-90% by weight of said one or more non-silicone biomedical device-forming monomers, based on a total weight of said biomedical device-forming mixture.

8. The biomedical device of claim 1, having an oxygen permeability (Dk) of at least 60.

9. The biomedical device of claim 1, which is one of a contact lens, an intraocular lens, and a hydrogel.

10. A method for making a biomedical device, comprising: (a) providing a biomedical device-forming mixture comprising: (i) one or more grafted glycosaminoglycan polymers comprising a glycosaminoglycan having a polymer backbone and one or more side chains comprising an ethylenically unsaturated reactant-containing residue grafted onto said polymer backbone; and (ii) one or more non-silicone biomedical device-forming monomers; (b) subjecting the mixture to polymerization conditions to provide a polymerized biomedical device; (c) hydrating the polymerized biomedical device; The method, wherein the biomedical device has a water content of at least 80% by weight.